Comparing the Efficacy and Safety of Cell Transplantation for Spinal Cord Injury: A Systematic Review and Bayesian Network Meta-Analysis - Xu, Xiongjie; Liang, Zeyan; Lin, Yike; Rao, Jian; Lin, Fabin; Yang, Zhelun; Wang, Rui; Chen, Chunmei (Frontiers in Cellular Neuroscience, 2022)
Objective: To compare the safety and effectiveness of transplanted cells from different sources for spinal cord injury (SCI). Design: A systematic review and Bayesian network meta-analysis. Data sources: Medline, Embase, and the Cochrane Central Register of Controlled Trials. Study selection: We included randomized controlled trials, case-control studies, and case series related to cell transplantation for SCI patients, that included at least 1 of the following outcome measures: American Spinal Cord Injury Association (ASIA) Impairment Scale (AIS grade), ASIA motor score, ASIA sensory score, the Functional Independence Measure score (FIM), International Association of Neurorestoratology Spinal Cord Injury Functional Rating Scale (IANR-SCIFRS), or adverse events. Follow-up data were analysed at 6 and 12 months. Results: Forty-four eligible trials, involving 1266 patients, investigated 6 treatments: olfactory ensheathing cells (OECs), neural stem cells/ neural progenitor cells (NSCs), mesenchymal stem cells (MSCs), Schwann cells, macrophages, and combinations of cells (MSCs plus Schwann cells). Macrophages improved the AIS grade at 12 months (mean 0.42, 95% confidence interval: 0‒0.91, low certainty), MSCs improved the AIS grade at 6 months (0.42, 0.15‒0.73, moderate certainty) and FIM score at 12 months (42.83, 36.33‒49.18, very low certainty), the motor score at 6 months (4.43, 0.91‒7.78, moderate certainty), light touch at 6 (10.01, 5.81‒13.88, moderate certainty) and at 12 months (11.48, 6.31‒16.64, moderate certainty), pinprick score at 6 (14.54, 9.76‒19.46, moderate certainty) and at 12 months (12.48, 7.09‒18.12, moderate certainty), and the IANR-SCIFRS at 6 (3.96, 0.62‒6.97, moderate certainty) and at 12 months (5.54, 2.45‒8.42, moderate certainty). OECs improved the FIM score at 6 months (-9.35, -17.00 to -1.71, moderate certainty). No intervention improved the motor score significantly at 12 months. The certainty of other interventions was low or very low. Overall, the number of adverse events associated with transplanted cells was low. Conclusions: Patients with SCI who receive transplantation of macrophages, MSCs, NSCs, or OECs may have improved disease prognosis. MSCs are the primary recommendations. Further exploration of the mechanism of cell transplantation in the treatment of SCI, transplantation time window, transplantation methods, and monitoring of the number of transplanted cells and cell survival is needed.